2020
DOI: 10.4269/ajtmh.19-0699
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Saharan Dust on Severe Small for Gestational Births in the Caribbean

Abstract: Desert dust transported from the Sahara to the Caribbean generates peak exposures to particulate matter £ 10 μm (PM 10). We investigated the impact of dust episodes on severe small for gestational-age births in Guadeloupe. The study sample consisted of 911 pregnant women enrolled in the Timoun mother-child cohort. Desert dust exposure was assessed through the mean daily PM 10 concentrations averaged over the entire pregnancy. Numerous sociodemographic and medical risk factors were considered as covariates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Viel et al (2019) looked at the association between Saharan dust intrusions and birth outcomes on the island of Guadeloupe, showing an association between mean PM 10 concentration and the proportion of intense dust events and preterm births. A follow-up study also found a relationship between increased PM 10 and low birth weight (Viel et al, 2020).…”
Section: Other Morbidity Effectsmentioning
confidence: 82%
“…Viel et al (2019) looked at the association between Saharan dust intrusions and birth outcomes on the island of Guadeloupe, showing an association between mean PM 10 concentration and the proportion of intense dust events and preterm births. A follow-up study also found a relationship between increased PM 10 and low birth weight (Viel et al, 2020).…”
Section: Other Morbidity Effectsmentioning
confidence: 82%
“…(2019) looked at the association between Saharan dust intrusions and birth outcomes on the island of Guadeloupe, showing an association between mean PM 10 concentration and the proportion of intense dust events and preterm births. A follow‐up study also found a relationship between increased PM 10 and low birth weight (Viel et al., 2020).…”
Section: Effects On Human Healthmentioning
confidence: 91%
“…Thus, the Caribbean are known to have some of the highest incidences of asthma on the planet due to dust outbreaks (Urrutia-Pereira et al, 2021). A recent study made by Viel et al (2020) in Guadeloupe also indicated that Saharan dust seems to influence weight but not length or head circumference at birth. For all the reasons aforementioned, it is therefore crucial to determine the detection threshold for African dust in the Caribbean basin.…”
Section: Introductionmentioning
confidence: 99%